EVALUATION OF EFFECTIVENESS OF HYPOALLERGENIC COMPOUND, ENRICHED WITH PREBIOTICS, FOR THE PROPHYLACTICS OF ATOPIC DERMATITIS - A.A. Dzhumagaziyev; D.A. Bezrukova; N.A. Stepina; A.B. Myasishcheva (Вопросы современной педиатрии, 2010)
The article presents a study of prophylactic effectiveness of hypoallergenic compound «Nutrilon Hypoallergenic 1», fortified with prebiotics «IMMUNOFORTIS», in children from group of risk of development of atopic dermatitis. Anthropometric rates of children after 8 weeks of observation corresponded with average age rates; their physical development was estimated as harmonious. The compound was well-tolerated. Its use resulted in increase of bifido- and lactobacteria of intestinal micro flora and decrease of acute respiratory infections in infants.Key words: infants, alimentary allergy, atopic dermatitis, artificial feeding, prebiotics, hypoallergenic compound.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(1):37-43)